Azo pigments and quinacridones induce delayed hypersensitivity in red tattoos. (2nd December 2014) - Gaudron, Sophie; Ferrier‐Le Bouëdec, Marie‐Christine; Franck, Frederic; D'Incan, Michel
Summary Background Induction of delayed hypersensitivity reactions by red tattoos has been occasionally reported. Little is known about the inks used. Azo pigments have been implicated in some instances, but there is only one reported case involving quinacridones. Objectives To describe the clinical and pathological features and outcome of skin reactions induced by red tattoo pigments. Patients, materials, and methods Six patients with a cutaneous reaction induced by a red tattoo pigment underwent biopsy and prick and patch testing with the inks supplied. Results We observed seven reactions in the 6 patients. Histology showed various patterns: three lichenoid, two eczematous, and two pseudolymphomatous. Five reactions occurred with azo pigments, and two with quinacridones, in both cases with Violet 19 and Red 122. Four inks were tested. Only one patch test gave a positive result at a late reading (day 7). Prick tests gave negative results. The reactions required various treatments, including laser treatment for 2 patients. Activation of the reaction in 1 case was transient. Conclusion Azo pigments and quinacridones both triggered reactions with similar clinical aspects but with varying histological findings. Patch and prick test results were disappointing with both. Reactions occurred following laser use in 1 case.